SISTEM APLIKASI PERANCANGAN E-COMMERCE BAHAN DAN ALAT UNTUK KEPERLUAN PRAKTEK DOKTER GIGI MENGGUNAKAN METODE RAD (Studi Kasus : CV. Jaya Mandiri Dental) - Adi Haidir Panji (PROCEEDING STIMA)
Sales online or E-Commerce is a mechanism separate businesses whose age was age corn. But here amazing side, for the first time all humans on earth have the same opportunity, in order to succeed in business in the virtual world. The purpose of this study is to provide application sales materials and tools dental practice that connects directly to the E-Commerce website online with information on goods or products, prices and how to purchase or payment so as to facilitate the user that a physician looking for materials and tools specific practice. The method used in this thesis is the RAD method that includes communications planning, design, implementation, and deployment. By using UML modeling, results achieved in the form of an E-Commerce website to search for materials and tools dental practice, as well as provide information needed for the order.Keyword : Website, E-Commerce, Sales Online, Dental, UML, RAD.